2021
DOI: 10.48550/arxiv.2112.07868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Few-shot Instruction Prompts for Pretrained Language Models to Detect Social Biases

Abstract: Warning: this paper contains content that may be offensive or upsetting.Detecting social bias in text is challenging due to nuance, subjectivity, and difficulty in obtaining good quality labeled datasets at scale, especially given the evolving nature of social biases and society. To address these challenges, we propose a few-shot instructionbased method for prompting pre-trained language models (LMs). We select a few labelbalanced exemplars from a small support repository that are closest to the query to be la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Additionally, these models also possess known (pre-deployment) safety issues for which we lack robust solutions [33] (e.g, How do you ensure the system does not generate inappropriate and harmful outputs, such as making overtly sexist or racist comments [65]? How do you identify bias issues in the system prior to deployment [8,53]? How do you ensure that when the model outputs a claim, it isn't making up facts [10]?, etc.…”
Section: Safetymentioning
confidence: 99%
“…Additionally, these models also possess known (pre-deployment) safety issues for which we lack robust solutions [33] (e.g, How do you ensure the system does not generate inappropriate and harmful outputs, such as making overtly sexist or racist comments [65]? How do you identify bias issues in the system prior to deployment [8,53]? How do you ensure that when the model outputs a claim, it isn't making up facts [10]?, etc.…”
Section: Safetymentioning
confidence: 99%
“…To draw a connection to computational ethics, Schick et al (2021) prompts GPT-2 and T5 for automated bias detection. (Prabhumoye et al, 2021) extends this line of research using more structured prompts and performed few-shot experiments across different classes of LLMs with varying sizes. In this work, we extend the zero-shot toxicity detection approach explore in previous work (Schick et al, 2021) to its generative variant and demonstrate its greater competence.…”
Section: Related Workmentioning
confidence: 88%
“…Automatic toxicity detection facilitates online moderation, which is an important venue for NLP research to positively impact the society. Recent works (Prabhumoye et al, 2021;Schick et al, 2021) demonstrate that large-scale pre-trained language models are able to detect toxic contents without fine-tuning. Prompts can be carefully designed to harness the implicit knowledge about harmful text learned by MLM pre-training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We follow the setting ofPrabhumoye et al (2022), which found that leveraging semantically close examples is effective for in-context learning. We use the vector space of all problem statements computed by Term Frequency-Inverse Document Frequency (TF-IDF) implemented in scikit-learn: https://tinyurl.com/scikitlearn-TF-IDF-vectorizer.…”
mentioning
confidence: 99%